Analisis Proses Bisnis dengan Menggunakan Business Process Model and Notation (Studi Kasus : Perum Perhutani Unit II Jawa Timur) - Ellen Yanuarti; Ismiarta Aknuranda; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Perum Perhutani is a state-owned company engaged in the forestry sector (in the forests of Java and Madura) and carries out the duties and authority to organize forest resource management activities (SDH) by taking into account aspects of production, economic aspects, social aspects and environmental aspects. Perum Perhutani uses Information Technology in carrying out its business processes, but does not yet have a Standard Operating Procedure (SOP) which is the benchmark and implementation of its activities. So that it is not clear yet the division of tasks in the activities of the business process and can hamper the purpose of a business process. Therefore, this topic to be studied specifically focusing on his business processes, production section, especially the production of teak and jungle. To find out where the problem, a model is needed. The business process model is needed to make it easier to understand the business processes that are currently running. Business processes are modeled using BPMN. The current business process problem is that only 3 actors are running on the business process so that it inhibits the current activity. After that, a proposed business process is made which involves 12 actors and additional activities.